Clade-1 Vap virulence proteins of Rhodococcus equi are associated with the cell surface and support intracellular growth in macrophages - Yerlikaya, Zeynep; Miranda-CasoLuengo, Raul; Yin, Yuting; Cheng, Cheng; Meijer, Wim G. (Public Library Science, 2025)
The multi-host pathogen Rhodococcus equi is a parasite of macrophages preventing maturation of the phagolysosome, thus creating a hospitable environment supporting intracellular growth. Virulent R. equi isolated from foals, pigs and cattle harbor a host-specific virulence plasmid, pVAPA, pVAPB and pVAPN respectively, which encode a family of 17 Vap proteins belonging to seven monophyletic clades. We examined all 17 Vap proteins for their ability to complement intracellular growth of a R. equi Delta vapA strain, and show that only vapK1, vapK2 and vapN support growth in murine macrophages of this strain. We show that only the clade-1 proteins VapA, VapK1, VapK2 and VapN are located on the R. equi cell surface. The pVAPB plasmid encodes three clade-1 proteins: VapK1, VapK2 and VapB. The latter was not able to support intracellular growth and was not located on the cell surface. We previously showed that the unordered N-terminal VapA sequence is involved in cell surface localisation of VapA. We here show that although the unordered N-terminus of the 17 Vap proteins is highly variable in length and sequence, it is conserved within clades, which is consistent with our observation that the N-terminus of clade-1 Vap proteins plays a role in cell surface localisation.
Keywords: Plasmid; Pathogenicity; Expression; Antigens; Survival